Stratification of yeast cells during chronological aging by size points to the role of trehalose in cell vitality - Svenkrtova, Andrea; Belicova, Lenka; Volejnikova, Andrea; Sigler, Karel; Jazwinski, S Michal; Pichova, Alena (Biogerontology, 2016)
Cells of the budding yeast Saccharomyces cerevisiae undergo a process akin to differentiation during prolonged culture without medium replenishment. Various methods have been used to separate and determine the potential role and fate of the different cell species. We have stratified chronologically-aged yeast cultures into cells of different sizes, using centrifugal elutriation, and characterized these subpopulations physiologically. We distinguish two extreme cell types, very small (XS) and very large (L) cells. L cells display higher viability based on two separate criteria. They respire much more actively, but produce lower levels of reactive oxygen species (ROS). L cells are capable of dividing, albeit slowly, giving rise to XS cells which do not divide. L cells are more resistant to osmotic stress and they have higher trehalose content, a storage carbohydrate often connected to stress resistance. Depletion of trehalose by deletion of TPS2 does not affect the vital characteristics of L cells, but it improves some of these characteristics in XS cells. Therefore, we propose that the response of L and XS cells to the trehalose produced in the former differs in a way that lowers the vitality of the latter. We compare our XS- and L-fraction cell characteristics with those of cells isolated from stationary cultures by others based on density. This comparison suggests that the cells have some similarities but also differences that may prove useful in addressing whether it is the segregation or the response to trehalose that may play the predominant role in cell division from stationary culture.
Keywords: Saccharomyces cerevisiae; trehalosa; Reactive Oxygen Species; Centrifugal elutriation; Trehalose; Cell size; Cellular Senescence; Yeast; Chronological aging; reaktivní formy kyslíku; stárnutí buněk